PARTISIPASI MASYARAKAT DALAM PERENCANAAN PEMBANGUNAN DI DESA AMBIA UTARA KECAMATAN ESSANG SELATAN KABUPATEN KEPULAUAN TALAUD - Laliboso, Sindi Yuliana; Pangkey, Masje; Londa, Very Yohanis (Sam Ratulangi University, 2025)
Abstract Community participation is a form of involvement of community members in all development which includes activities in planning and implementing development programs. Community participation in This form of participation supports the success of programs provided by the government.There are several forms of participation that the community can provide in a development program, namely money participation, property participation, energy participation, skills participation, idea participation, social participation, participation in the decision-making process, and representative participation. Of the varios forms of participation mentioned above, participation can be grouped into 2 types, namely forms of participation that are given in a real form (having a form) and also forms of participation that are given in an intangible foem (abstract). Tangible forms of participation include money, property, energy and skills, while intangible form of participation, social participation, decision making and representative participation. The aim of this research is to determine Community Prticipation in Development Planning in North Ambia Village. This research uses qualitative descriptive research methods. Data collection techniques used were observation, interviews and data collection with documents. Based on the results of research examined by researchers through observation, data collection and interview processes in Development Planning in North Ambia Village, South Essang District, Talaud Islands Regency, it is still not good. The community itself needs to increase awareness about participating in development planning in decision making, musrembang and participation in implementation. Keywords: Society, Participation, Development, Planning